Graphical Methods for Investigating the Size and Power of Hypothesis Tests - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 1994)
Simple techniques for the graphical display of simulation evidence concerning the size and power of hypothesis tests are developed and illustrated. Three types of figures - called P value plots, P value discrepancy plots, and size-power curves - are discussed. Some Monte Carlo experiments on the properties of alternative forms of the information matrix test are used to illustrate these figures. Tests based on the OPG regression are found to perform poorly in terms of both size and power.
Keywords: 330